On International Law Protection of Child Sexual Assault: Also on Protection of Children's Rights in China - Wu, Haonan; Wang, Jun (International Journal of Social Sciences and Public Administration, 2024)
The spate of child sexual abuse has raised awareness of the need and urgency to protect children from sexual abuse. In international law, sexuality is increasingly linked to human rights and is increasingly recognized as a fundamental human right, and the Convention on the Rights of the Child highlights the perspective of sexual human rights. We have ratified the Convention on the Rights of the Child and the Optional Protocol to the Convention on the Rights of the Child on the sale of children, child prostitution and child pornography. But let's face it, there are still many children in the world who are being sexually abused. To this end, we should sum up our experience, improve relevant laws in light of national conditions, and build a comprehensive and multi-level system for the protection of children's sexual rights, so as to provide a safe and harmless environment for children's growth.